Exercise during pregnancy and its impact on mothers and offspring in humans and mice. (7th August 2017) - Ferrari, N.; Bae-Gartz, I.; Bauer, C.; Janoschek, R.; Koxholt, I.; Mahabir, E.; Appel, S.; Alejandre Alcazar, M. A.; Grossmann, N.; Vohlen, C.; Brockmeier, K.; Dötsch, J.; et al.
Abstract : Exercise during pregnancy has beneficial effects on maternal and offspring's health in humans and mice. The underlying mechanisms remain unclear. This comparative study aimed to determine the long-term effects of an exercise program on metabolism, weight gain, body composition and changes in hormones [insulin, leptin, brain-derived neurotrophic factor (BDNF)]. Pregnant women ( n =34) and mouse dams ( n =44) were subjected to an exercise program compared with matched controls (period I). Follow-up in the offspring was performed over 6 months in humans, corresponding to postnatal day (P) 21 in mice (period II). Half of the mouse offspring was challenged with a high-fat diet (HFD) for 6 weeks between P70 and P112 (period III). In period I, exercise during pregnancy led to 6% lower fat content, 40% lower leptin levels and an increase of 50% BDNF levels in humans compared with controls, which was not observed in mice. After period II in humans and mice, offspring body weight did not differ from that of the controls. Further differences were observed in period III. Offspring of exercising mouse dams had significantly lower fat mass and leptin levels compared with controls. In addition, at P112, BDNF levels in offspring were significantly higher from exercising mothers while this effect was completely blunted by HFD feeding. In this study, we found comparable effects on maternal and offspring's weight gain in humans and mice but different effects in insulin, leptin and BDNF. The long-term potential protective effects of exercise on biomarkers should be examined in human studies.